Stress Induced Immune Dysregulation: A Continuum Spanning Antarctica Winterover, Spaceflight, and Terrestrial Patients - Sams, Clarence; Krieger, Stephanie; Strewe, Claudia; Chouker, Alexander; Pierson, Duane; Makedonas, George; Crucian, Brian; Feuerecker, Matthias; Mehta, Satish; Nelman, Mayra; Tyring, Stephen (2019)
Spaceflight is a unique environment characterized by stress, microgravity, isolation, circadian misalignment, and radiation exposure and impacts immune health. Planned long duration missions to Mars are a top priority for NASA and mitigating the negative health consequences of spaceflight is particularly important. Terrestrial analogs are a vital aspect of spaceflight research since data from astronauts is limited and it is costly to receive samples from ISS. The most relevant ground analog would include station lifestyle, stress, disrupted circadian rhythms and isolation. This analysis compares various aspects of immune dysregulation in astronauts during long-duration orbital spaceflight to groundanalogs. Astronaut data were also compared to a clinical immunodeficiency population, shingles patients, to help interpret clinical risks during deep space missions. A comprehensive evaluation was performed across hypoxic interior Antarctica, normoxic coastal Antarctica, HERA, and astronauts which included plasma and mitogen stimulated cytokine profiles, T-cell function, and peripheral leukocyte distribution. A cross platform analysis was then performed to define in-flight immune alterations, determine analog appropriateness, and interpret clinical risk.